(3GdPQjYI Edi CUhd Gdabgs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEffj QCjJ Cf Cedj cJGHG eJhSWG aj CUhd Gdabg dG jfJgj HJWhjd (B... (3hdG HGNJUGQ Edi GdENdGd Hd jchf ddMGLI SOGO (B...s
(3BNQgG (B:s
... (3GdWQjbI deG Yde GdYbdGA HQGAI Peege ef GdMbhb hfMf ddBf bGWYhf cJGHfG gPG abO GfJgjfG ajg (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B4 / 278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs